Biocontrol Efficacy Of Native Trichoderma Strains Isolated From Farm And Forest Soil Against Collar Rot (Sclerotium Rolfsii) Of Lentil (SAARC Journal of Agriculture, 2024)
Lentil, Lens culinaris is an important pulse crop of Nepal which is susceptible to collar rot disease caused by Sclerotium rolfsii during its early growth stages. The fungus attacks the collar region of the plant, causing rotting of the stem resulting in stunted growth, wilting and reduced productivity. Additionally, it weakens the plant, making them more susceptible to other diseases and stresses such as drought. The pathogen can survive in the soil for extended periods by producing sclerotia. Trichoderma species are known for their antagonistic ability against diverse plant pathogens, including S. rolfsii. This study was conducted to identify promising native Trichoderma isolates for controlling collar rot of lentil during 2020 and 2021 in Chitwan, Nepal. A total of 104 Trichoderma isolates collected from farm and sal, Shorea robusta forest soil and examined in vitro by dual culture technique against S. rolfsii in a completely randomized design. Of them, 30 isolates were selected to study biocontrol potential under a screen house by inoculating both the pathogen and Trichoderma onto lentil seedlings. Subsequently, four promising Trichoderma isolates were selected representing different agro-ecological regions for the field trial in a randomized complete block design to assess their ability to control S. rolfsii in field conditions. Results showed that Trichoderma isolates T73, Forest soil (96.96%); T74, Forest soil (94.49%) and T62, Darchula (88.92%) had shown strong inhibition of S. rolfsii growth, with forest soil isolates exhibiting higher antagonistic potential. In the screen house assay, all Trichoderma isolates increased seed germination, enhanced plant growth, and reduced disease incidence as compared to the control. Trichoderma isolates T49, Bhaktapur, and T31, Banke showed the highest percentage of disease control and percentage yield increase in the field conditions. These findings highlight the consistent potential of Trichoderma for biocontrol of collar rot diseases in lentil.SAARC J. Agric., 22(1):169-179  (2024)